Impact of angiotensin receptor blocker as antihypertensive in assessing mortality in patients of COVID-19: A single tertiary care center study - Sourya Acharya; Sunil Kumar; Ruchita Kabra; Mansi Patel; Neha Phate; Dhruv Talwar; Varun Daiya (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The angiotensin-converting enzyme 2 (ACE2) receptor, a membrane receptor present in the respiratory system, the gastrointestinal tracts, the heart, and the kidney is the entry point for SARS-CoV-2 to enter human cells. Concerns were raised about the influence of using antihypertensive drugs like angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) in individuals with COVID-19 due to its tight relationship with the ACE2 receptor. The aim of this study was to investigate the impact of being on an Angiotensin Receptor Blockers (ARB) on mortality in patients consecutively diagnosed with COVID-19. MATERIAL AND METHODS: This is the retrospective observational study done in all patients consecutively diagnosed with COVID-19 from January 2021 to June 2021. All related patient information and clinical data was retrieved from the hospitals electronic medical record system. RESULTS: In this study, out of 500 patients, 51 died, having mean age of 66.92 ± 10.85 years. 144 (28.8%) patients were on angiotensin receptor blockers as antihypertensive treatment, 142 (28.4%) having other antihypertensive and 214 (42.8%) were not on any treatment. Out of 51 Death 7 (4.9) patients were on ARBs, 15 ± 10.6 were on other medication [OR 2.31 (0.94-6.22, P = 0.077) univariable; OR 2.57 (1.00-7.23, P = 0.058) multivariable] and 29 ± 13.6 had no treatment at all [OR 3.07 (1.38-7.80, P = 0.010) univariable; OR 3.36 (1.41-9.08, P = 0.010) multivariable]. CONCLUSION: Use of ARB medications for the hypertensive patients who acquire COVID-19 infection has shown protective effects of such medications on COVID-19 disease severity in the term of mortality and the mortality rate among hypertensive patients on COVID-19 with ARBs/ACE inhibitors showed significant differences as compared to other antihypertensives.